Lessons learnt from MDM2 fluorescence in‐situ hybridisation analysis of 439 mature lipomatous lesions with an emphasis on atypical lipomatous tumour/well‐differentiated liposarcoma lacking cytological atypia. Issue 2 (11th November 2021) - Vargas, Ana Cristina; Joy, Christopher; Cheah, Alison L; Jones, Martin; Bonar, Fiona; Brookwell, Ross; Garrone, Bernadette; Talbot, Joel; Harraway, James; Gill, Anthony J; Maclean, Fiona M
Abstract : Aims: Amplification of the murine double minute‐2 (MDM2) gene, which is usually detected with fluorescence in‐situ hybridisation (FISH), is the key driving event for atypical lipomatous tumours (ALTs)/well‐differentiated liposarcomas (WDLs). We sought to determine the concordance between the histopathological findings and MDM2 FISH in the diagnosis of ALT/WDL, and to identify the histological features of MDM2 ‐amplified tumours lacking classic atypia. Methods and results: We performed a retrospective analysis of all mature lipomatous lesions subjected to MDM2 FISH analysis at our institution. MDM2 FISH analysis was performed on 439 mature lipomatous lesions: 364 (82.9%) were negative and 75 (17%) were positive. In 17 of 75 (22.6%) ALTs/WDLs, cytological atypia was not identified on initial histological assessment, thus favouring lipoma. On review, these cases shared common histological features, consisting of a very low number of relatively small stromal cells within the tumour lobules, with mildly coarse chromatin and oval nuclei, admixed with unremarkable adipocytes in a tumour background devoid of fibroconnective septa, areas of fibrosis, or blood vessels. These cells matched the cells in which FISH showed MDM2 amplification. In contrast, 13 cases (3.5%) regarded as suspicious for ALT/WDL on the basis of histology lacked MDM2 amplification and were reclassified following the FISH findings. Conclusions: We conclude that a subset of lipoma‐like ALTs/WDLs are not associated with any of the features typically described in ALT/WDL. Our study also showed that tumours >100 mm are more likely to be ALT/WDL; however, a history of recurrence or concerning clinical/radiological features was not significantly associated with classification as ALT/WDL. Abstract :